Energy-Neutral Scheduling and Forwarding in Environmentally-Powered Wireless Sensor Networks - VALERA, Alvin Cerdena (Institutional Knowledge at Singapore Management University, 2013)
In environmentally-powered wireless sensor networks (EPWSNs), low latency wakeup scheduling and packet forwarding is challenging due to dynamic duty cycling, posing time-varying sleep latencies and necessitating the use of dynamic wakeup schedules. We show that the variance of the intervals between receiving wakeup slots affects the expected sleep latency: when the variance of the intervals is low (high), the expected latency is low (high). We therefore propose a novel scheduling scheme that uses the bit-reversal permutation sequence (BRPS) – a finite integer sequence that positions receiving wakeup slots as evenly as possible to reduce the expected sleep latency. At the same time, the sequence serves as a compact representation of wakeup schedules thereby reducing storage and communication overhead. But while low latency wakeup schedule can reduce per-hop delay in ideal conditions, it does not necessarily lead to low latency end-to-end paths because wireless link quality also plays a significant role in the performance of packet forwarding. We therefore formulate expected transmission delay (ETD), a metric that simultaneously considers sleep latency and wireless link quality. We show that the metric is left-monotonic and left-isotonic, proving that its use in distributed algorithms such as the distributed Bellman–Ford yields consistent, loop-free and optimal paths. We perform extensive simulations using real-world energy harvesting traces to evaluate the performance of the scheduling and forwarding scheme.